2021
DOI: 10.3390/ijms221810050
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Magnolol, a Lignan from Magnolia Bark, in Diabetes, Its Complications and Comorbidities—A Review

Abstract: Diabetes mellitus is a chronic metabolic disease characterized by disturbances in carbohydrate, protein, and lipid metabolism, often accompanied by oxidative stress. Diabetes treatment is a complicated process in which, in addition to the standard pharmacological action, it is necessary to append a comprehensive approach. Introducing the aspect of non-pharmacological treatment of diabetes allows one to alleviate its many adverse complications. Therefore, it seems important to look for substances that, when inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 143 publications
(236 reference statements)
0
16
0
Order By: Relevance
“…Although magnolol has multiple biological activities, including the prevention and amelioration of diseases such as cancer ( 13 ), anti-depressant ( 14 ) and anti-diabetes ( 15 ) effects, and improvement of growth performance ( 16 ), its potential activity against bacterial diseases has not been fully explored. In this study, we unexpectedly found that magnolol exhibits potent potentiation (8- to 64-fold) of the effectiveness of cefquinome against resistant bacteria, even at high magnolol concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although magnolol has multiple biological activities, including the prevention and amelioration of diseases such as cancer ( 13 ), anti-depressant ( 14 ) and anti-diabetes ( 15 ) effects, and improvement of growth performance ( 16 ), its potential activity against bacterial diseases has not been fully explored. In this study, we unexpectedly found that magnolol exhibits potent potentiation (8- to 64-fold) of the effectiveness of cefquinome against resistant bacteria, even at high magnolol concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Magnolol is an extractive from Houpo (Magnolia officinalis), which was first recorded in the Shennong Herbal Classic. As shown in previous studies, magnolol has multiple biological activities, including the prevention and amelioration of diseases such as cancer (13), anti-depressant (14) and anti-diabetes (15) effects, and improvement of growth performance (16). However, the Ben Cao Gang Mu (Compendium of Materia medica) indicates gastrointestinal tract diseases such as dysentery and cholera as indications for Houpo, which suggests that Houpo interacts with the intestinal flora.…”
Section: Introductionmentioning
confidence: 96%
“…Remarkably, magnolol, a natural component from magnolia bark [23], stood out as a PPARγ stabilizer without side effects. Magnolol has been found to be beneficial for systemic health, such as reducing hyperglycemia, decreasing hyperlipidemia, and being anticancer [24][25][26]. Previous reports have also suggested a protective function of magnolol on insulin resistance by enhancing adipogenesis, although the mechanism was not illuminated [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have also suggested a protective function of magnolol on insulin resistance by enhancing adipogenesis, although the mechanism was not illuminated [27,28]. The multifaceted pharmacological effects of magnolol involve the regulation of phosphoinositide-3-kinase/Akt serine/threonine kinase 1 (Akt), mitogen-activated protein kinase (MAPK), and nuclear factor-κB (NF-κB) pathways [24][25][26]. However, the regulatory mechanism of PPARγ by magnolol is not illustrated yet, which is critical for improved medicine development.…”
Section: Introductionmentioning
confidence: 99%
“…Magnolol is thus a plant-derived, natural compound that shows promising effects in the prevention and treatment of T2D and its complications. The authors suggest magnolol may be a good supportive compound complementing conventional therapeutic methods in counteracting diabetic negative effects on the organism [ 6 ]. The herbal tea, rooibos, produced from Aspalathus linearis , is the only dietary source to date of aspalathin, a flavonoid and C -glucosyl dihydrochalcone.…”
mentioning
confidence: 99%